FUNGSI OLAH TEMPAT KEJADIAN PERKARA (TKP) GUNA MENGUNGKAPKAN KASUS PENGANIAYAAN BERAT DITINJAU DARI SUDUT HUKUM ACARA PIDANA - Lestari Victoria Sinaga; Mhd. Yuda Mulyawan Simatupang (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study aims at revealing cases of severe maltreatment through crime scene crime scenes. One of the investigation processes can convince the investigator in determining the suspect in handling the crime scene (TKP) where it is divided into 2 namely the First Actions at the crime scene (TPTKP) and processing of the crime scene (olah TKP) from the legislation. As for the results obtained are the methods used by public observations, sketches and photographs, handling victims, handling witnesses and suspects and handling evidence through CCTV footage. In cases of severe maltreatment from the crime scene results can be used through other tools- others such as watering the face with Lombok water, acidic substances, sulfur, saltpeter, vinegar, so that the skin on the face burns, or inserting poisons in food. Not only can it be proven analytically or through autopsy, but it depends on the performance of criminal investigators at the crime scene and eyewitness examination.